Approach to Managing Periodic Discharges. Issue 4 (July 2018) - Bauerschmidt, Andrew; Rubinos, Clio; Claassen, Jan
Abstract : Summary: Use of continuous EEG monitoring in the intensive care unit setting has increased detection of not only subclinical seizures, but also patterns of discharges that have epileptiform features and periodicity yet do not meet the criteria for seizures. These periodic discharges present a clinical challenge: some patterns may reflect brain injury that has already occurred, although there is evidence that some periodic discharges represent an ongoing process causing additional brain injury and necessitate treatment. Herein, we review the available data regarding the clinical significance of different categories of periodic discharges, specifically those that have features physiologically similar to seizures. We propose a stepwise approach to assessment and management of periodic discharges and lay out the general paradigm of (1) clinical assessment including benzodiazepine trial, (2) EEG assessment, with a focus on discharge frequency, and (3) integration of adjunctive data such as neuroimaging and metabolic data when available. A flowchart is provided to simplify and summarize this approach. The goal of this approach is to treat patterns associated with increased risk of seizures and/or additional brain injury, while avoiding unnecessary interventions.